The Identification of a Novel Calcium-Dependent Link Between NAD+ and Glucose Deprivation-Induced Increases in Protein O-GlcNAcylation and ER Stress - Zou, Luyun; Collins, Helen E.; Young, Martin E.; Zhang, Jianhua; Wende, Adam R.; Darley-Usmar, Victor M.; Chatham, John C. (Frontiers in Molecular Biosciences, 2021)
The modification of proteins by O-linked -N-acetylglucosamine (O-GlcNAc) is associated with the regulation of numerous cellular processes. Despite the importance of O-GlcNAc in mediating cellular function our understanding of the mechanisms that regulate O-GlcNAc levels is limited. One factor known to regulate protein O-GlcNAc levels is nutrient availability; however, the fact that nutrient deficient states such as ischemia increase O-GlcNAc levels suggests that other factors also contribute to regulating O-GlcNAc levels. We have previously reported that in unstressed cardiomyocytes exogenous NAD+ resulted in a time and dose dependent decrease in O-GlcNAc levels. Therefore, we postulated that NAD+ and cellular O-GlcNAc levels may be coordinately regulated. Using glucose deprivation as a model system in an immortalized human ventricular cell line, we examined the influence of extracellular NAD+ on cellular O-GlcNAc levels and ER stress in the presence and absence of glucose. We found that NAD+ completely blocked the increase in O-GlcNAc induced by glucose deprivation and suppressed the activation of ER stress. The NAD+ metabolite cyclic ADP-ribose (cADPR) had similar effects on O-GlcNAc and ER stress suggesting a common underlying mechanism. cADPR is a ryanodine receptor (RyR) agonist and like caffeine, which also activates the RyR, both mimicked the effects of NAD+ and cADPR. SERCA inhibition, which also reduces ER/SR Ca2+ levels had similar effects to both NAD+ and cADPR on O-GlcNAc and ER stress responses to glucose deprivation. The observation that NAD+, cADPR, and caffeine all attenuated the increase in O-GlcNAc and ER stress in response to glucose deprivation, suggests a potential common mechanism, linked to ER/SR Ca2+ levels, underlying their activation. Moreover, we showed that TRPM2, a plasma membrane cation channel was necessary for the cellular responses to glucose deprivation. Collectively, these findings support a novel Ca2+-dependent mechanism underlying glucose deprivation induced increase in O-GlcNAc and ER stress.